Causes of nursing home placement for older people with dementia: a systematic review and meta-analysis - Toot, Sandeep; Swinson, Tom; Devine, Mike; Challis, David; Orrell, Martin (Cambridge University Press, 2016)
Background: Up to half of people with dementia in high income countries live in nursing homes and more than two-thirds of care home residents have dementia. Fewer than half of these residents report good quality of life and most older people are anxious about the prospect of moving into a nursing home. Robust evidence is needed as to the causes of admission to nursing homes, particularly where these risk factors are modifiable. Methods: We conducted a systematic literature search to identify controlled comparison studies in which the primary outcome was admission to nursing home of older adults with dementia. Identified studies were assessed for validity and 26 (17 cohort and 9 case-control) were included. Qualitative and quantitative analyses were conducted, including meta-analysis of 15 studies. Results: Poorer cognition and behavioral and psychological symptoms of dementia (BPSD) were consistently associated with an increased risk of nursing home admission and most of our meta-analyses demonstrated impairments in activities of daily living as a significant risk. The effects of community support services were unclear, with both high and low levels of service use leading to nursing home placement. There was an association between caregiver burden and risk of institutionalization, but findings with regard to caregiver depression varied, as did physical health associations, with some studies showing an increased risk of nursing home placement following hip fracture, reduced mobility, and multiple comorbidities. Conclusion: We recommend focusing on cognitive enhancement strategies, assessment and management of BPSD, and carer education and support to delay nursing home placement.